ChemInform Abstract: Synthesis of Multiply Arylated Heteroarenes, Including Bioactive Derivatives, via Palladium‐Catalyzed Direct C—H Arylation of Heteroarenes with (Pseudo)Aryl Halides or Aryliodonium Salts. Issue 3 (January 2015) - Rossi, Renzo; Bellina, Fabio; Lessi, Marco; Manzini, Chiara; Perego, Luca A.
Abstract Review: [228 refs.